Comprehensive analysis of morbidity and mortality patterns in familial partial lipodystrophy patients: insights from a population study - Guidorizzi, Natália Rossin; Valerio, Cynthia M.; Viola, Luiz F.; Veras, Victor Rezende; Fernandes, Virgínia Oliveira; Lima, Grayce Ellen da Cruz Paiva; Flor, Amanda Caboclo; Araújo, Jessica Silveira; Gonçalves Muniz, Raquel Beatriz; Moreira, Rodrigo Oliveira; De Paula, Francisco José Albuquerque; Zajdenverg, Lenita; et al. (Frontiers in Endocrinology, 2024)
Background: There is a lack of information on the clinical and molecular presentation of familial partial lipodystrophy (FPLD), a rare genetic disorder characterized by partial subcutaneous fat loss.Objective: This study aimed to provide a comprehensive assessment of the clinical, metabolic, and genetic features of FPLD in the Brazilian population.Methods: In a multicenter cross-sectional investigation we evaluated patients with FPLD across five Brazilian reference centers for lipodystrophies. Diagnosis of FPLD was made by clinical evaluation and genetic confirmation. Data on genetic, clinical, and metabolic characteristics were captured. Statistical analysis involved the utilization of the Kruskal-Wallis test to identify differences.Results: The study included 106 patients with genetic confirmation of FPLD. The mean age was 44 ±15 years, and they were predominantly female (78.3%). LMNA pathogenic variants were identified in 85.8% of patients, PPARG in 10.4%, PLIN1 in 2.8%, and MFN2 in 0.9%.Diabetes mellitus (DM) was highly prevalent (57.5%), affecting 54 females (50.9%). Median triglycerides levels were 199 mg/dL (54-2724 mg/dL), severe hypertriglyceridemia (≥ 500 mg/dL) was found in 34.9% and pancreatitis in 8.5%. Metabolic-associated fatty liver disease (MAFLD) was observed in 56.6%, and cardiovascular disease in 10.4%. The overall mortality rate was 3.8%, due to cardiovascular events. Conclusion: This study presents an extensive cohort of Brazilian patients with FPLD, predominantly DM with several multisystem complications. A comprehensive characterization of lipodystrophy syndromes is crucial for effective patient management and care.